Rekonstruksi Konsep Wali Mujbir: Analisis Maqasid Syariah dan Konteks Sosial Kontemporer di Indonesia - Nailul Muna Fadhli; Akhmad Muhaini; Arifuat Marzuki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The opinions of the Salaf scholars on Islamic law, especially marriage, have been widely criticized by Muslim scholars today because they are considered irrelevant and violate women's rights. One of the study materials that has received attention lately is the concept of wali mujbir. This problem is felt to always roll and develop every time if the law is formulated without knowing the mindset and perspective of Islamic law itself. The purpose of this study is to determine the construction of Wali Mujbir in Islamic law and to find its context in the contemporary era using Maqasid Syariah and the social context in Indonesia. In this study, it was found that the concept of wali mujbir has lost its relevance and context in the contemporary era when viewed through maqasid syariah. Through a literature review by considering the social context, this study reveals the relevance and context of Wali Mujbir in Indonesia in order to achieve the maslahah summarized in al-kulliyat al-khoms. The author tries to combine text sources and opinions of Salaf-contemporary scholars so that there is no liberalization of the law but remains within the framework of revelation. Thus, this study provides an overview of the concept of Wali Mujbir and finds its context and essence in contemporary Islamic law.